Morphological Variability of the Cotton Boll Weevil in the Principal Cotton-Growing Region of Argentina - Garcia, Carolina Vanesa (2025)
The cotton boll weevil (Anthonomus grandis grandis Boheman) (Coleoptera: Curculionidae) is the main pest of the cotton (Gossypium hirsutum Linnaeus) (Malvaceae) crop in South America. First reported in Argentina in 1993, it rapidly dispersed throughout the main cotton-growing region, severely impacting the crop production. However, little is known about the external morphometry and variability of these populations. The main objective of the present study was to assess morphological variability among five boll weevil populations collected in the main cotton-growing region of Argentina during two seasons (winter and growing seasons) using traditional morphometry. Nine morphological variables were measured in 30 individuals per population. Sexual dimorphism was not detected for any of the variables. Significant differences among populations were found based on location and season of collection. Principal component analysis (PCA) and a dendrogram revealed that winter populations clustered together, showing intermediate morphological values and low variability across the three sampled localities. Populations collected during the growing season grouped into two distinct clusters: one comprising populations from the Chaco province and the other from the remaining locations. One-way ANOVA further supported these patterns, indicating significant differences among Anthonomus grandis grandis populations for “elytra length” and “total body length” variables. The results were discussed in relation to climatic conditions, cotton management practices, and alternative food sources, providing morphological records that could help optimize control strategies. Larger individuals, likely key reproducers, may require early control, whereas smaller ones may reflect suboptimal development due to limited nutritional resources or high intraspecific competition. These traits may also affect the survival of overwintering populations. Overall, these findings contribute to a better understanding of boll weevil population dynamics and their implications for integrated pest management.